Potentials of prophylaxis of idiopathic antibiotic-associated diarrhea in adults - I. V. Mayev; N. Yu. Ivashkina; A. A. Samsonov; A. N. Kazyulin; Ye. S. V’yuchnova; A. M. Shuster; V. A. Mart’yanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To evaluate efficacy of application of probiotic drug Acipol®, containing acidophilic lactobacilli and kefiric fungi inactivated by warmingup, in prophylaxis of antibiotic-associated diarrhea in adults.Materials and methods. Prospective, randomized, comparative open study included 225 patients. Patients of the main group (n=150) received Acipol® 1 capsule bid for 2 wks along with antibiotics. Patients of the control group (n=75) took no probiotic drug. At development of diarrhea investigation for ruling out of its contagious origin was carried out. After cessation of antibiotics patients reported cases of diarrhea for the following 4 wks.Results. Frequency of antibiotic-associated diarrhea at patients of the control group in prospective investigation was 12%, in retrospective study – 2%, i.e. in real practice non-diagnosed cases of antibiotic-associated diarrhea in adult patients at hospital stay, make on average 10%. Of patients of the main group receiving probiotic, mild diarrhea was diagnosed only in 1 patient (0,7%).Conclusions. Preventive application of the Acipol® in adults concurrently with antibiotics reduces risk of antibiotic-associated diarrhea on the average by 11,3%.